Ridership estimation of a new LRT system: Direct demand model approach. (January 2017) - Kepaptsoglou, Konstantinos; Stathopoulos, Antony; Karlaftis, Matthew G.
Abstract: The successful introduction of LRT systems is inevitably related to the realistic estimation of their ridership; this is particularly true for cases of no prior experience in the use of such modes in the part of the traveling public. This paper presents a practical approach for developing a direct demand model, for the case of a planned LRT system in Cyprus connecting the three major cities of Nicosia, Larnaca and Limassol. The proposed approach is based on existing traffic demand data and limited roadside surveys. Results indicate that the introduction of the proposed LRT would attract a moderate number of 23, 000 passengers daily and shift a small percentage of 3.5% of traffic to the system. It was also found that approximately 33% of these trips correspond to the urban section of the network, while about 62% of the estimated ridership will use the part of the system connecting Nicosia and Larnaca. Highlights: Direct Demand Models (DDM) are low cost, efficient alternatives to FSM. A DDM based methodology is developed for estimating ridership of a planned LRT. Existing traffic data and limited RSS information are used for model development. The model is applied for a planned LRT system in Cyprus.